ANALISIS FAKTOR SOSIAL EKONOMI YANG MEMPENGARUHI PRODUKSI PETANI KOPI SANGGABUANA DI KECAMATAN TEGALWARU KABUPATEN KARAWANG - Rusmawati - Utami; Abubakar Abubakar; I Putu Eka Wijaya (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2022)
Karawang Regency has potential in coffee production, this is shown by the increase in land area in 2018 and 2019 by 0.024 ha with a production value of 207.20 tons in the same year with a productivity value of 0.50 Karawang compared to the Pangandaran area which experienced a decline. land area of 12.14 ha and has an increased production value from 2018 to 2019 of 15.60 tons with a productivity value of 0.44. The low coffee production in Tegalwaru District is because farmers who cultivate coffee are still simple, such as the absence of plant care, no fertilizer and pesticides are applied, it is necessary to research on socio-economic factors on production in Tegalwaru District, Karawang Regency. The purpose of this research is to determine the partial and simultaneous influence of socio-economic factors that affect coffee production. Samples were determined using the Slovin formula, sampling using themethod simple random sampling. The analysis technique used is multiple regression analysis, classical assumption test and hypothesis testing. The results showed that the simultaneous hypothesis testing of independent variables (land area, labor age, length of farming, number of dependents, and education) jointly affected the dependent variable (production). In the partial test, only the land area variable has a partial effect on production.